An improved equivalent-input-disturbance approach for PMSM drive with demagnetization fault. (October 2020) - Huang, Gang; Li, Jiajun; Fukushima, Edwardo F.; Zhang, Changfan; He, Jing; Zhao, Kaihui
Abstract: Closed-loop torque control system of permanent magnet synchronous motor (PMSM) drive is highly applied in industrial applications. However, high temperature and other external factors lead to permanent magnet (PM) demagnetization fault of the motor, which inevitably brings barriers to precise torque control. This paper presents a rejection method for demagnetization based on an improved equivalent-input-disturbance (EID) approach. A system model, which contains demagnetization fault, is first constructed. Then, an equivalent-input-demagnetization on the control input channel is used to describe the model. An improved EID approach is designed to reject the effect of the demagnetization fault. In particular, an improved sliding-mode observer rather than the Luenberger observer in a conventional EID theory is designed to estimate the equivalent-input-demagnetization. This greatly enhances the response speed and accuracy of the estimation and rejection, and then effectively improves the accuracy of torque tracking. Finally, the step change and the ramp change of a demagnetization are introduced into a hardware-in-the-loop experiment, separately. Comparisons with other methods show the effectiveness of the method. Highlights: An EID theory is firstly introduced to deal with the rejection of demagnetization in a PMSM drive. The method effectively avoids the problem of the reconfiguration of the controller. This guarantees the stability of the original system. An improved SMO replaces a Luenberger observer in the conventional EID approach. This greatly improves the estimation accuracy of equivalent-input demagnetization and the robustness of the PMSM drive. A ramp change of the demagnetization fault model is employed in the experiment. This is considered to justify the effectiveness of the method in the case of real PM demagnetization.